Increasing Small Businesses in the Home Chips Industry by Boosting Quality and Market Reach - Ati, Nurul Umi; Mahardhika, Brahmadhita Pratama; Pinastika, Prajna Paramita; Nuriyanti, Ika; Ingsih, Ita Suhermin (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Small home industry businesses (UKMRT) play a crucial role in the economy by providing income for marginalized families with limited capital. In Kedungkandang, Malang City, UKMRT, especially cassava chip producers, face challenges such as limited equipment, a lack of hygienic production knowledge, and poor financial management. This study employed Participatory Action Research (PAR) to address these issues by engaging the community in problem identification and solution implementation. Training sessions focused on financial management, hygienic production techniques, and marketing strategies. Introducing modern cassava-cutting tools and improved packaging significantly enhanced production efficiency and product appeal. Results indicated increased production capacity, higher product quality, and improved financial practices among partners. The economic impact was evident as daily income for producers increased substantially, and marketing expanded beyond local markets from 200 thousand rupiahs per day to 500 thousand rupiahs. This holistic approach, integrating economic, social, and technological aspects, highlights the potential for significant socio-economic transformation in similar communities. Further geographical expansion and product diversification are recommended to sustain and enhance these positive outcomes. The study demonstrates a replicable model for community service that effectively addresses the multifaceted needs of small home industry businesses.